Reversal of Cancer Multidrug Resistance (MDR) Mediated by ATP-Binding Cassette Transporter G2 (ABCG2) by AZ-628, a RAF Kinase Inhibitor - Wang, Jing-Quan; Teng, Qiu-Xu; Lei, Zi-Ning; Ji, Ning; Cui, Qingbin; Fu, Han; Lin, Lizhu; Yang, Dong-Hua; Fan, Ying-Fang; Chen, Zhe-Sheng (Frontiers in Cell and Developmental Biology, 2020)
Overexpression of ABCG2 remains a major impediment to successful cancer treatment, because ABCG2 functions as an efflux pump of chemotherapeutic agents and causes clinical multidrug resistance (MDR). Therefore, it is important to uncover effective modulators to circumvent ABCG2-mediated MDR in cancers. In this study, we reported that AZ-628, a RAF kinase inhibitor, effectively antagonizes ABCG2-mediated MDR in vitro. Our results showed that AZ-628 completely reversed ABCG2-mediated MDR at a non-toxic concentration (3 μM) without affecting ABCB1-, ABCC1- or ABCC10 mediated MDR. Further studies revealed that the reversal mechanism was by attenuating ABCG2-mediated efflux and increasing intracellular accumulation of ABCG2 substrate drugs. Moreover, AZ-628 stimulated ABCG2-associated ATPase activity in a concentration-dependent manner. Docking and molecular dynamics simulation analysis showed that AZ-628 binds to the same site as ABCG2 substrate drugs with higher score. Taken together, our studies indicate that AZ-628 could be used in combination chemotherapy against ABCG2-mediated MDR in cancers.